Interaction of indigenous minority peoples: resilience and sustainable development of remote and hard-to-reach territories - Filippova, Viktoriya V.; Kuklina, Maria V.; Trufanov, Andrey I.; Savvinova, Antonina N.; Krasnoshtanova, Natalia E.; Fedorova, Alla S.; Itegelova, Anna P.; Kobylkin, Dmitry V. (The New Research of Tuva, 2024)
The article examines the territorial relations of the Tuvan-Todzhin residents of Todzhinsky Kozhuun in the Republic of Tuva, the Soyots of Okinsky District in the Republic of Buryatia, the Tofalars of Nizhneudinsky District in the Irkutsk Region, the Evenks of Tyndinsky District in the Amur Region, and the Neryungrinsky District in the Sakha Republic (Yakutia). These areas are home to indigenous minority groups from different regions of Russia, who live in remote and hard-to-access territories. The research aims to find the optimal set of indicators for sustainable development at the local level for indigenous communities that preserve traditional forms of environmental management. The authors believe that this can be achieved through the application of a meta-disciplinary approach, using ontologies, models, and indicators to show the consistency of economic, ecological, ethnocultural, and social aspects. Three types of social connections are identified in the topological field: family (kinship) relationships, cultural interaction, and economic activity. Traditional life support is also considered. The main conclusion is the stratification and detailed analysis of connections between residents based on the type and scale of their interactions.